2001
DOI: 10.1177/002204260103100111
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Drug Use and Crime among Offenders: The Impact of Graduated Sanctions

Abstract: The evaluation of the Washington, D.C., Superior Court Drug Intervention Program (SCDIP) compared drug felony defendants randomly assigned to either a docket offering structured graduated sanctions in combination with drug testing and judicial monitoring, or a docket using drug tests and judicial monitoring only. Assignment to the graduated sanctions docket was found to reduce drug use prior to sentencing. Program participants were significantly less likely to use drugs prior to sentencing, and, in the year af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…Researchers have argued that such techniques should be paired with schedules of reinforcement that include certain and swift consequences (Boyum, Caulkins, & Kleiman, 2010;Harrell & Roman, 2001;Taxman, Soule, & Gelb, 1999). Indeed, the variable coupling of these components have benefitted participants of residential therapeutic communities (Inciardi, Martin, & Butzin, 2004;Knight, Simpson, & Hiller, 1999;Martin, Butzin, Saum, & Inciardi, 1999;Wexler, Melnich, Lowe, & Peters, 1999), drug courts (Belenko, 2001;Harrell, Mitchell, Hirst, Marlowe, & Merrill, 2002;Harrell & Roman, 2001;Gottfredson, Najaka, & Kearley, 2003), and community-based substance abuse treatment (Center for Substance Abuse Research, 1994;Friedmann, Rhodes, & Taxman, 2009) with observed improvement in relapse, revocation, or recidivism outcomes. Community-based supervision strategies similarly benefitted from the integration of behavioral management and reinforcement approaches (Friedmann et al, 2009;Taxman, 2008;Wodahl, Garland, Culhane, & McCarty, 2011).…”
mentioning
confidence: 99%
“…Researchers have argued that such techniques should be paired with schedules of reinforcement that include certain and swift consequences (Boyum, Caulkins, & Kleiman, 2010;Harrell & Roman, 2001;Taxman, Soule, & Gelb, 1999). Indeed, the variable coupling of these components have benefitted participants of residential therapeutic communities (Inciardi, Martin, & Butzin, 2004;Knight, Simpson, & Hiller, 1999;Martin, Butzin, Saum, & Inciardi, 1999;Wexler, Melnich, Lowe, & Peters, 1999), drug courts (Belenko, 2001;Harrell, Mitchell, Hirst, Marlowe, & Merrill, 2002;Harrell & Roman, 2001;Gottfredson, Najaka, & Kearley, 2003), and community-based substance abuse treatment (Center for Substance Abuse Research, 1994;Friedmann, Rhodes, & Taxman, 2009) with observed improvement in relapse, revocation, or recidivism outcomes. Community-based supervision strategies similarly benefitted from the integration of behavioral management and reinforcement approaches (Friedmann et al, 2009;Taxman, 2008;Wodahl, Garland, Culhane, & McCarty, 2011).…”
mentioning
confidence: 99%
“…The U.S. Bureau of Justice Statistics estimates that about half of both federal prisoners and jail inmates abuse, or are dependent on, drugs (Mumola and Karberg 2006). Few, however, received treatment within the criminal justice system (Harrell and Roman 2001). Among incarcerated populations, only about 15% received drug treatment (Karberg and James 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Under the rubric of therapeutic jurisprudence, a more formal model of intensive court-based supervision, referred to as drug-treatment courts, emerged in the 1990s (Hora et al 1999;Senjo and Leip 2001;Slobogin 1995;Wexler and Winick 1991). A number of studies have found that drug-treatment court participation reduces recidivism rates (Finigan 1998;Goldkamp and Weiland 1993;Gottfredson and Exum 2002;Harrell and Roman 2001;Peters and Murrin 2000;Wilson et al 2006). The courts first appeared in Miami, Florida, but by 2005 there were about 600 adult drug courts in operation in the United States, and similar programs have been implemented in several other nations, including Australia, Barbados, Bermuda, Brazil, Canada, Cayman Islands, Chile, Ireland, Jamaica, Norway, Scotland, Trinidad and Tobago, and the United Kingdom (UNODC 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several commentators have suggested that the success of drug courts might be accounted for by the theory of ''perceived deterrence'' (e.g., Harrell & Roman, 2001;Hora, Schma, & Rosenthal, 1999;Marlowe & Kirby, 1999). Perceived-deterrence theory posits that most people engage in a form of rational ''cost/benefit analysis'' when deciding whether or not to engage in illegal or inappropriate conduct.…”
mentioning
confidence: 99%
“…Perceived-deterrence theory posits that most people engage in a form of rational ''cost/benefit analysis'' when deciding whether or not to engage in illegal or inappropriate conduct. The calculus of the cost/benefit ratio is believed to involve a consideration of (1) the perceived certainty of being detected for infractions, (2) the perceived certainty of receiving a sanction for infractions, and (3) the anticipated magnitude of the sanctions (see, e.g., Gibbs, 1975;Harrell & Roman, 2001;Tittle, 1980;Zimrig & Hawkins, 1973). Although classical deterrence theory typically focuses on the avoidance of negative behaviors, in its broadest formulation it also involves a rational consideration of the costs and benefits of engaging in pro-social behaviors in lieu of negative behaviors (for example, obtaining a job in lieu of committing a robbery).…”
mentioning
confidence: 99%